THE RELATIONSHIP OF QUOTIENT ADVERSITY WITH ACADEMIC PROCRASTINATION STUDENT COUNSELING GUIDANCE PROGRAM UNIVERSITAS PATTIMURA - Rahmat F. Tuasikal; Emma Rumahlewang; Valensia Tutupary (Peneliti.net, 2019)
Academic Procrastination is a delay that is done to start and complete tasks related to academics. Particularly the problem of procrastination occurred at a student who studied guidance and counseling. This research aims to know is there any adversity quotient relations with academic procrastination. The method used is descriptive quantitative data analysis techniques using statistics analysis techniques, correlation formula product moment of pearson. The subject of the study amounted to 27 students. The conclusions of this writing is there’s a significant relationship between the adversity quotient with Academic Procrastination however, it is a negative relationship between the adversity quotient with the academic procrastination, the more high level of adversity quotient someone then procrastination will be getting lower. In contrast the lower the adversity quotient higher procrastination. The average score category adversity quotient high, score procrastination academic is medium.